2023
DOI: 10.1109/jlt.2023.3241449
|View full text |Cite
|
Sign up to set email alerts
|

On the Nonlinear Shaping Gain With Probabilistic Shaping and Carrier Phase Recovery

Abstract: The performance of different probabilistic amplitude shaping (PAS) techniques in the nonlinear regime is investigated, highlighting its dependence on the PAS block length and the interaction with carrier phase recovery (CPR). Different PAS implementations are considered, based on different distribution matching (DM) techniques-namely, sphere shaping, shell mapping with different number of shells, and constant composition DM-and amplitude-to-symbol maps. When CPR is not included, PAS with optimal block length p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, the performance improvement obtained by em- ploying short-block-length DMs becomes nearly irrelevant when carrier phase recovery (CPR) is included in the system, as in all practical systems. Indeed, we have shown that also CPR mitigates some nonlinear interference-in fact, the same nonlinear interference that is avoided by reducing the PAS blocklength-improving the performance of all DMs and hiding the nonlinear shaping gain provided by short block length PAS in many practical scenarios [20]. This behaviour is predicted by the nonlinear phase noise (NPN) metric, which, differently from EDI, Kurtosis, and LSAS, allows to account also for the impact of CPR [20].…”
Section: A Nonlinear Performance Of Conventional Dmmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the performance improvement obtained by em- ploying short-block-length DMs becomes nearly irrelevant when carrier phase recovery (CPR) is included in the system, as in all practical systems. Indeed, we have shown that also CPR mitigates some nonlinear interference-in fact, the same nonlinear interference that is avoided by reducing the PAS blocklength-improving the performance of all DMs and hiding the nonlinear shaping gain provided by short block length PAS in many practical scenarios [20]. This behaviour is predicted by the nonlinear phase noise (NPN) metric, which, differently from EDI, Kurtosis, and LSAS, allows to account also for the impact of CPR [20].…”
Section: A Nonlinear Performance Of Conventional Dmmentioning
confidence: 97%
“…The modulation format is dual polarization 64-QAM with probabilistic shaping and root-raised-cosine supporting pulse with rolloff 0.05. As a benchmark, and as a starting point (referred to as unbiased source) for sequence selection, we consider probabilistic amplitude shaping (PAS) with rate R 4D = 9.2 bit/4D (equivalent to R DM = 1.3 bit/amplitude), implemented with the serial mapping for quadratures and polarizations [20]. The signal is sent into a link composed of 30 × 100 km spans of single mode fiber (SMF) with erbiumdoped fiber amplifiers (EDFAs) with noise figure 5 dB.…”
Section: System Descriptionmentioning
confidence: 99%
See 3 more Smart Citations